PENERAPAN PEMBELAJARAN BERBASIS SCAFFOLDING TERHADAP CARA BERPIKIR KREATIF SISWA KELAS VIII-2 SMP NEGERI 12 KOTA TANGGERANG SELATAN - lina marlina (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2024)
ABSTRACT Learning requires a process, including when students learn something, it requires a process of creative thinking so that a teacher's assistance is needed by students. This research aims to see how the scaffolding-based learning process is applied to students' creative thinking, especially in subjects of Pancasila. The target of this research is class VIII-2 students at SMPN 12 South Tanggerang City, using a qualitative approach research method through the stages of observation, interviews, and documentation carried out by the researcher. From the results of this research, the application of scaffolding-based learning to students' creative thinking can be successful, said to be successful because, with scaffolding-based learning, students who previously did not know and could not finally know can do so with gradual assistance from educators gradually students can learn it independently and by themselves students can easily understand the learning material so that enable students to think more creatively.